The Influence of Online Game Mobile Legends: Bang Bang on Interpersonal Communication in Gen Z - Ari Muhammad Luthfi (Cita konsultindo, 2025)
Online games are a type of video game that requires the internet when using it, this gives the possibility of players interacting with each other in real time. This study aims to analyze whether there is an influence of mobile legends online games on interpersonal communication among generation Z and if it affects how much influence it has on interpersonal communication among gen z. The study population was unknown so it used the lemeshow formula and obtained a sample size of 86 people according to the criteria (Gen Z). The study population was unknown so it used the lemeshow formula and obtained a sample size of 86 people according to the criteria (Gen Z). The data analysis method uses simple linear regression by first conducting a classical assumption test. The results showed that there was an effect of the Mobile Legends Online Game: Bang Bang on Interpersonal Communication among Generation Z of 0.286, which means that the use of Online Games by Gen Z contributes to the influence on the high and low (variation in value) on the Interpersonal Communication variable in Gen Z by 28.6%, while the contribution outside the variable of 71.4% of Interpersonal Communication in Gen Z is due to other variables not included in this study..